Metabolomic study of saxitoxin analogues and biosynthetic intermediates in dinoflagellates using (15)N-labelled sodium nitrate as a nitrogen source - Cho, Yuko (Sci Rep, 2019)
A stable-isotope-labelling method using (15)N-labelled sodium nitrate as a nitrogen source was developed for the toxic dinoflagellate Alexandrium catenella. The labelled saxitoxin analogues (STXs), their precursor, and the biosynthetic intermediates were analyzed by column-switching high-resolution hydrophilic interaction liquid chromatography with mass spectrometry. The low contents on Day 0, high (15)N incorporation % of Int-C’2 and Int-E’ suggested that their turn-over rates are high and that the sizes of the pool of these compounds are smaller than those of the other intermediates. The experimentally determined isotopomer distributions showed that arginine, Int-C’2, 11-hydroxy-Int-C’2, Int-E’, GTX5, GTX4, C1, and C2, each existed as a combination of three populations that consisted of the non-labelled molecules and the labelled isotopomers representing molecules newly synthesized by incorporation of (15)N assimilated from the medium with two different incorporation rates. The order of (15)N incorporation % values of the labelled populations predicted by this model largely agreed with the proposed biosynthetic route. The stable-isotope-labelling method will be useful for understanding the complex mechanism of nitrogen flux in STX-producing dinoflagellates.